INTERNATIONAL COMMUNITY PARTNERSHIP: STRENGTHENING LIVESTOCK COOPERATIVE INSTITUTIONS THROUGH PHILIPPINES–INDONESIA KNOWLEDGE TRANSFER ON ANIMAL WASTE MANAGEMENT - Lia Muliawaty; Ine Mariane; Marifa Alifah Oktafiani; Rina Karlina (Jurnal Abdisci, 2026)
Background. This Community Service Program (PKM) focuses on an international community partnership aimed at strengthening livestock cooperative institutions through Philippines–Indonesia knowledge transfer on animal waste management. Methods. Service activities are centered on the beef cattle and dairy farming hub in Kuningan Regency. The main problems faced by the partner, the Karya Nugraha Jaya Multi-Purpose Cooperative (KSU KNJ), include suboptimal management of cattle manure waste, limited knowledge among members and administrators regarding biogas technology, weak institutional capacity to provide educational services, and high dependence of farmers on conventional energy. Poorly managed livestock waste causes significant environmental pollution and represents a lost economic opportunity. Result. The proposed solution is a participatory and educational community empowerment approach centered on strengthening cooperative institutions. Key strategies include intensive outreach on the role of cooperatives in biogas technology and strengthening cooperative institutional mechanisms covering management, participatory decision-making, transparency, and partnerships. Mandatory program outputs include scientific publication in an ISSN-registered journal, publication in mass media, and a joint publication presenting the Indonesia–Philippines case study. Conclusion. Key success indicators are the controlled management of accumulated waste, improved post-training knowledge assessment scores on biogas among participants, and the cooperative's ability to independently manage its operations. Implementation. This program is expected to improve farmers' economic welfare through energy cost savings and additional income from liquid organic fertilizer (LOF), while also supporting national renewable energy mix targets.